No woods so dark as these [large type] - Silvis, Randall, 1950- (Silvis, Randall, 1950- Ryan DeMarco mystery, 2021)
"The nightmarish discovery of a body inside a smoldering car is only made worse when, hours later, a naked man is found nailed to a tree. Two murders in the small Pennsylvania town is unheard of, so retired sergeant Ryan DeMarco and his partner Jayme are called in once again to untangle a thick web of lies, betrayal, and desperation that cloaks their corner of the world. As they dig deeper into the investigation, DeMarco finds that, out of everything he has seen, this case might be the one that breaks him for good."--